Emotion dysregulation and autonomic responses to film, rumination, and body awareness: Extending psychophysiological research to a naturalistic clinical setting and a chemically dependent female sample. (2nd March 2017) - Crowell, Sheila E.; Price, Cynthia J.; Puzia, Megan E.; Yaptangco, Mona; Cheng, Sunny Chieh
Abstract: Substance use is a complex clinical problem characterized by emotion dysregulation and daily challenges that can interfere with laboratory research. Thus, few psychophysiological studies examine autonomic and self‐report measures of emotion dysregulation with multidiagnostic, chemically dependent samples or extend this work into naturalistic settings. In this study, we used a within‐subject design to examine changes in respiratory sinus arrhythmia (RSA), electrodermal activity (EDA), and self‐reported affect across three tasks designed to elicit distinct psychophysiological and emotional response patterns. We also examined emotion dysregulation as a moderator of psychophysiological responses. Participants include 116 women with multiple comorbid mental health conditions enrolled in substance use treatment, many of whom also reported high emotion dysregulation. Participants were assessed in the treatment setting and completed three tasks: watching a sad movie clip, rumination on a stressful event, and a mindful interoceptive awareness meditation. Multilevel models were used to examine changes from resting baselines to the tasks. During the film, results indicate a significant decrease in RSA and an increase in EDA. For the rumination task, participants showed a decrease in RSA but no EDA response. For the body awareness task, there was an increase in RSA and a decrease in EDA. Emotion dysregulation was associated with differences in baseline RSA but not with EDA or with the slope of response patterns across tasks. Self‐reported affect was largely consistent with autonomic patterns. Findings add to the literature on emotion dysregulation, substance use, and the translation of psychophysiological measurements into clinical settings with complex samples.